The first genome sequence of a metatherian herpesvirus: Macropodid herpesvirus 1. (December 2016) - Vaz, Paola; Mahony, Timothy; Hartley, Carol; Fowler, Elizabeth; Ficorilli, Nino; Lee, Sang; Gilkerson, James; Browning, Glenn; Devlin, Joanne
Abstract Background While many placental herpesvirus genomes have been fully sequenced, the complete genome of a marsupial herpesvirus has not been described. Here we present the first genome sequence of a metatherian herpesvirus, Macropodid herpesvirus 1 (MaHV-1). Results The MaHV-1 viral genome was sequenced using an Illumina MiSeq sequencer, de novo assembly was performed and the genome was annotated. The MaHV-1 genome was 140 kbp in length and clustered phylogenetically with the primate simplexviruses, sharing 67 % nucleotide sequence identity withHuman herpesviruses 1 and2 . The MaHV-1 genome contained 66 predicted open reading frames (ORFs) homologous to those in other herpesvirus genomes, but lacked homologues of UL3, UL4, UL56 and glycoprotein J. This is the first alphaherpesvirus genome that has been found to lack the UL3 and UL4 homologues. We identified six novel ORFs and confirmed their transcription by RT-PCR. Conclusions This is the first genome sequence of a herpesvirus that infects metatherians, a taxonomically unique mammalian clade. Members of theSimplexvirus genus are remarkably conserved, so the absence of ORFs otherwise retained in eutherian and avian alphaherpesviruses contributes to our understanding of theAlphaherpesvirinae. Further study of metatherian herpesvirus genetics and pathogenesis provides a unique approach to understanding herpesvirus-mammalian interactions.